2021
DOI: 10.5334/bc.125
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and comparison of densification effects and planning motivations

Abstract: Do higher urban densities contribute to more sustainable cities and communities? This paper examines the effectiveness of higher density (as a means) for achieving sustainable urban development (the goal) following three lines of enquiry. First, a systematic review of the scientific literature (n = 229 peer-reviewed empirical studies) is presented on the effects of urban density. Second, the motivations for increasing urban density are studied in a systematic review of Swedish planning practices based on the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 124 publications
0
10
0
Order By: Relevance
“…Swedish municipalities are legally obliged to clarify how they plan to use land and water resources; how the built environment should be used, developed and conserved; and how the municipality will secure national interests and comply with environmental quality regulations [9]. The comprehensive plan is the document in which planners attempt to negotiate conflicting goals [2,10,11]. In comprehensive plans, ecosystem services are often outlined as prerequisites for successful densification.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Swedish municipalities are legally obliged to clarify how they plan to use land and water resources; how the built environment should be used, developed and conserved; and how the municipality will secure national interests and comply with environmental quality regulations [9]. The comprehensive plan is the document in which planners attempt to negotiate conflicting goals [2,10,11]. In comprehensive plans, ecosystem services are often outlined as prerequisites for successful densification.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of holism is relevant, as it points to the fact that urban planning is not merely about a political will to merge all good values but a conscious understanding of how changing one factor in a city may affect another. Berghauser Pont et al [10] analysed 59 Swedish comprehensive plans and demonstrated that while densification has positive effects on public infrastructure, transport and economy, there were negative environmental, social and health impacts. Naess et al [5], in a more theoretical article, critically discussed how urban densification is conceptually aligned with ecological modernisation, where de-coupling economic growth from environmental limitations makes it theoretically possible to combine densification with a lush environment.…”
Section: Introductionmentioning
confidence: 99%
“…According to this research, positive effects exist for public infrastructure, transport, and economics, while there are considerable negative environmental, social and health impacts. Related to health issues, particularly negative effects on mental health are associated with densification, where the compactness of the built fabric and the lack of open space plays an important role when explaining perceived urban stress [13]. Furthermore, sustainability within planning and building is still strongly associated with the green dimension, further reinforced by concerns about climate change, while social aspects are less discussed.…”
Section: Introductionmentioning
confidence: 99%
“…While governments worldwide rely on densification policies to reduce land consumption from urban growth, possible ecological, economic and social effects of urban densification are being widely discussed (Berghauser Pont et al, 2021). Many of these effects are not inherent to densification – they manifest in some cases but not in others.…”
Section: Introductionmentioning
confidence: 99%